If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14+16=-5(6x-6)
We move all terms to the left:
14+16-(-5(6x-6))=0
We add all the numbers together, and all the variables
-(-5(6x-6))+30=0
We calculate terms in parentheses: -(-5(6x-6)), so:We get rid of parentheses
-5(6x-6)
We multiply parentheses
-30x+30
Back to the equation:
-(-30x+30)
30x-30+30=0
We add all the numbers together, and all the variables
30x=0
x=0/30
x=0
| 2x-8+x/17=39 | | -17+72=-5(x+4) | | −8/9=v−1/2 | | −89=v−21 | | 6(x+2)/5=4x-2 | | 6-3(4x+1)=15-10x | | 3y+7-7=5+2y+2 | | 10x+7=72 | | 6+18m=(-16m)-40-4 | | (8)(3)m=2 | | 6u^2-26u+20=0 | | 7m-12m-11=3(m-2) | | (-8,2)m=2 | | -3(x+7)=-6x-6 | | -2x+16=6(x-8) | | -12x+2(x-5)+7x=5x-50 | | 5x/2-2=4 | | -8(v+6)=3v-26 | | -12x+2(x-5)=7x=5x-50 | | (x/4)*6^1028=537 | | -8v=5v+15 | | -5x+8x-14=3(x-4)-34 | | X2-y2=12Y+24 | | -6t+12=-2(3t+6) | | z-3.8/0.2=-3 | | 2.4x1-1.08x2=0 | | -1/2(5k-20)=95 | | 4a-7=2a+9 | | 8x-8x=-4 | | 2+(9+m)=(2+9)+m=11+m | | x÷7=-2 | | 3/5+7/6x=1/8x |